Beauty in the silence [compact disc] - J Boog, 1983-; Buddz, Collie; Velasco, Camile; Campbell, Ali, 1959-; Stick Figure; Básico, Nanpa; Swanson, Eric (ATO Records, 2021)
For more than two decades, SOJA have elated audiences across the globe with their fresh yet timeless take on roots reggae, a sound born from their shared passion for making music that transports and inspires. On their first new album in four years, the two time Grammy-nominated band deepens that communal spirit by collaborating with artists from all corners of the reggae world, including UB40, Slightly Stoopid, Dirty Heads, and Rebelution.